Species diversity and distribution patterns of the ants of Amazonian Ecuador. - Kari T Ryder Wilkie (Public Library of Science (PLoS), 2010)
Ants are among the most diverse, abundant and ecologically significant organisms on earth. Although their species richness appears to be greatest in the New World tropics, global patterns of ant diversity and distribution are not well understood. We comprehensively surveyed ant diversity in a lowland primary rainforest in Western Amazonia, Ecuador using canopy fogging, pitfall traps, baits, hand collecting, mini-Winkler devices and subterranean probes to sample ants. A total of 489 ant species comprising 64 genera in nine subfamilies were identified from samples collected in only 0.16 square kilometers. The most species-rich genera were Camponotus, Pheidole, Pseudomyrmex, Pachycondyla, Brachymyrmex, and Crematogaster. Camponotus and Pseudomyrmex were most diverse in the canopy, while Pheidole was most diverse on the ground. The three most abundant ground-dwelling ant genera were Pheidole, Solenopsis and Pyramica. Crematogaster carinata was the most abundant ant species in the canopy; Wasmannia auropunctata was most abundant on the ground, and the army ant Labidus coecus was the most abundant subterranean species. Ant species composition among strata was significantly different: 80% of species were found in only one stratum, 17% in two strata, and 3% in all three strata. Elevation and the number of logs and twigs available as nest sites were significant predictors of ground-dwelling ant species richness. Canopy species richness was not correlated with any ecological variable measured. Subterranean species richness was negatively correlated with depth in the soil. When ant species were categorized using a functional group matrix based on diet, nest-site preference and foraging ecology, the greatest diversity was found in Omnivorous Canopy Nesters. Our study indicates ant species richness is exceptionally high at Tiputini. We project 647-736 ant species in this global hotspot of biodiversity. Considering the relatively small area surveyed, this region of western Amazonia appears to support the most diverse ant fauna yet recorded.